A prospective longitudinal study of BK virus infection in 120 Czech renal transplant recipients - Girmanova, Eva; Brabcova, Irena; Bandur, Stepan; Hribova, Petra; Skibova, Jelena; Viklicky, Ondrej (Journal of medical virology, 2011)
Polyomavirus BK (BKV) is a common human polyomavirus that rarely causes clinical symptoms in immunocompetent individuals. However, BK virus reactivation occurs in 20-40% of kidney transplant patients and 1-10% of cases present with BK virus-associated nephropathy (BKVN) and reduced kidney allograft survival. In this study, 120 consecutive renal allograft recipients were monitored for BK virus replication by real-time PCR (qPCR) in the blood and urine during the first year post-transplantation and risk factors for BK viremia, viruria, and polyoma BKV-associated nephropathy were evaluated. Receiver operating characteristic curve analysis was used to determine the cutoff points for assessing the risk of developing BKVN. In total, 1,243 samples were tested. BK-DNAuria >10(7) copies/ml and BK-DNAemia >10(4) copies/ml were found in 25.8% and 5% of the samples screened, respectively, during the 12 month follow-up period. BKVN was confirmed histologically in 3/120 patients and viremic patients were treated with dialysis for longer time periods and had higher levels of panel [corrected] reactive antibodies. Patients with viruria were also treated longer with dialysis and had impaired graft function 12 months post-transplantation. Patients with sustained viruria exhibited more acute rejection episodes than patients with transient viruria. Using receiver operating characteristic curve analysis, the cutoff point for viremia and viruria was redefined to 10(3) copies/ml serum for BK viremia and a cutoff point of 6.7 × 10(7) copies/ml in urine. In conclusion, polyoma BK viremia and viruria are frequent findings in kidney transplant recipients that warrant intensive monitoring as a means of preventing graft failure [corrected].
Keywords: senioři; Blood; Urine; longitudinální studie; Transplantation; transplantace ledvin; Prognosis; mladiství; Middle Aged; ROC Curve; Renal Dialysis; mužské pohlaví; Prospective Studies; Adult; mladý dospělý; Polyomavirus Infections; polyomavirové infekce; ROC křivka; krev; Young Adult; moč; ženské pohlaví; prognóza; BK Virus; Kidney Transplantation; Humans; prospektivní studie; virus BK; transplantace; lidé středního věku; rizikové faktory; dialýza ledvin; Longitudinal Studies; dospělí; Female; Aged; Risk Factors; Adolescent; lidé; Male